(untitled) (Journal of Education and Development, 2023)
Institutional internationalization arose as a globalized cross-cultural organizational practice in all social sectors. Popularity of the concept in the higher education sector urged authors to present numerous descriptions of internationalization approaches, which differed according to the philosophical references, circumstances of applying in the academic environments, and means–ends analysis. In the Third World countries, universities used to confront enormous challenges hindering internationalization ambitions in the context of structural and functional obstacles facing development in general. Perhaps it can be said that their internationalization is almost impossible in light of the complex socio- economic environments in those countries, political crises, obsolete bureaucracy, institutional inertia, and restricted academic freedoms. In any case, universities around the world are currently dealing with internationalization as an undebatable issue and must be working on it as a competitive requirement and substantive standard for quality assurance in higher education. In this article, the authors argue the success potential of an organizational transformation-based strategy to internationalization established on institutional adaptation and capacity building. This strategy has been adopted as a transitional stage between localization and internationalization in Nawroz University (NZU) which is presented here as a case study. NZU, as one of the private universities that following the local academic administration system in Kurdistan region of Iraq, has been faced complications resulted from the responsibility of tracking balance between fostering international values and policies, on the one hand, as well as maintaining institutional stability and human resources’ positive response to the change, on the other hand. The article discusses how this university dealt with the idea of harmonization as a result of awareness of the difficulties implied in the task of internationalization. Therefore, it adopted what it had considered as a consistent, sustainable, and gradual institutional transformation during the period (2016-2019). The article also highlights plans taken up to support skill up-gradation to consolidate implicit transformation without affecting everyday workflow. In addition, it refers to some simulated international approaches and rankings standards which were used as a guide to direct the transformational process. Finally, the article illustrates some preferable outcomes that the university has been achieved.